1988
DOI: 10.1007/bf02395514
|View full text |Cite
|
Sign up to set email alerts
|

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis

Abstract: Extensive heterogeneity in particle size distribution of serum lipoproteins of baboons was resolved by a procedure that combined Sudan black B prestaining, polyacrylamide gradient gel electrophoresis (GGE), and quantitative densitometry. Each densitometric scan represented a continuous distribution of the relative amount of cholesterol in a serum sample, as a function of the lipoprotein particle size. For analytical purposes, each scan was divided into 12 fractions, representing 12 particle size ranges. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…LDL-C absorbance profiles from densitometric scans of gradient gels were fractionated into 4 subclasses as described in Methods. Several previous studies have reported a linear response of Sudan Black B staining to the amount of cholesterol in HDL and its subfractions, [33][34][35] although there appeared to be a consistent difference in chromogenicities of LDLs and HDLs (ie, amount of stain bound per unit of cholesterol). 35 Figure 1 shows the results of such comparisons for 11 pairs of samples.…”
Section: Measurement Of Cholesterol In Ldl Size Fractionsmentioning
confidence: 92%
See 1 more Smart Citation
“…LDL-C absorbance profiles from densitometric scans of gradient gels were fractionated into 4 subclasses as described in Methods. Several previous studies have reported a linear response of Sudan Black B staining to the amount of cholesterol in HDL and its subfractions, [33][34][35] although there appeared to be a consistent difference in chromogenicities of LDLs and HDLs (ie, amount of stain bound per unit of cholesterol). 35 Figure 1 shows the results of such comparisons for 11 pairs of samples.…”
Section: Measurement Of Cholesterol In Ldl Size Fractionsmentioning
confidence: 92%
“…Several previous studies have reported a linear response of Sudan Black B staining to the amount of cholesterol in HDL and its subfractions, [33][34][35] although there appeared to be a consistent difference in chromogenicities of LDLs and HDLs (ie, amount of stain bound per unit of cholesterol). 35 Figure 1 shows the results of such comparisons for 11 pairs of samples. The cholesterol concentrations in size fractions from the samples run separately (ie, expected) showed a strong linear relationship with those observed in the mixture (r 2 ϭ0.991), and the slope (0.93Ϯ0.01) and y intercept (0.4Ϯ0.1 nmol) were close to 1 and 0, respectively, which would be the expectation if all LDLs have identical chromogenicities.…”
Section: Measurement Of Cholesterol In Ldl Size Fractionsmentioning
confidence: 92%
“…15 The absorbance profile with Sudan black staining was also assumed to closely reflect the cholesterol distribution among LDL particles of different sizes. 16 Thus, the absolute concentration of cholesterol among particles Ͻ255 Å was calculated by multiplying the total plasma LDL cholesterol levels by the relative proportion of LDL with a diameter Ͻ255 Å. A similar approach was used to assess the relative and absolute concentrations of cholesterol in particles with a diameter Ͼ260 Å.…”
Section: Ldl Particle Size Characterizationmentioning
confidence: 99%
“…It has been documented that Sudan black stains mainly non-polar lipids [15]. The absorbance profile with Sudan black staining was also assumed to closely reflect the cholesterol distribution among LDL particles of different sizes [16]. The absolute concentration of cholesterol among particles smaller than 255 Å was calculated by multiplying plasma LDL cholesterol levels by the relative proportion of LDL with a diameter smaller than 255 Å.…”
Section: Methodsmentioning
confidence: 99%